2009
DOI: 10.1098/rsta.2008.0297
|View full text |Cite
|
Sign up to set email alerts
|

In silico biology of bone modelling and remodelling: adaptation

Abstract: Modelling and remodelling are the processes by which bone adapts its shape and internal structure to external influences. However, the cellular mechanisms triggering osteoclastic resorption and osteoblastic formation are still unknown. In order to investigate current biological theories, in silico models can be applied. In the past, most of these models were based on the continuum assumption, but some questions related to bone adaptation can be addressed better by models incorporating the trabecular microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 69 publications
(101 reference statements)
1
39
0
Order By: Relevance
“…This remodelling takes place for a prolonged period of time, gradually reverting the blood supply to a normal state and restoring the bone at the regeneration site to its original shape and strength. More information on the biology and in silico modelling of the remodelling process can be found elsewhere in this issue (Gerhard et al 2009). …”
Section: Bone Regeneration (A ) Biology Of Bone Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…This remodelling takes place for a prolonged period of time, gradually reverting the blood supply to a normal state and restoring the bone at the regeneration site to its original shape and strength. More information on the biology and in silico modelling of the remodelling process can be found elsewhere in this issue (Gerhard et al 2009). …”
Section: Bone Regeneration (A ) Biology Of Bone Regenerationmentioning
confidence: 99%
“…The calculated tissue-level mechanical stimuli are used to adapt the biological parameters, whereas in reality a substantial difference is measured between tissue-level and cellular-level stimuli. You et al (2001) proposed a model to explain (and calculate) the observed strain amplification phenomenon in the osteocytes' processes (see also Gerhard et al 2009). These osteocytes are considered the main mechanosensors in bone (Mullender & Huiskes 1997;Burger & Klein-Nulend 1999).…”
Section: Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first validation step was to carefully visually check the registration result by overlying segmented baseline and transformed follow-up images into one image and color-code the result [34] for all patients. The quality of the registration was further quantified by the final value of the correlation coefficient between images.…”
Section: D Registration Accuracymentioning
confidence: 99%
“…The temporal changes in bone microarchitecture and material properties attributed to age, disease and treatment have not yet been incorporated into FE simulations. However, several computational approaches exist that attempt to simulate these catabolic and anabolic changes in bone as reviewed elsewhere (Gerhard et al 2009). While these models are not yet fully validated, they could be integrated into a multiscale approach aimed at monitoring the long-term fracture risk of patients.…”
Section: Bone Remodellingmentioning
confidence: 99%